Pengaruh Pengungkapan Akuntansi Lingkungan Dan Mekanisme Good Corporate Governance Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Dinal Eka Pertiwi; Ahmad Junaidi; Furqonti Ranidiah; Nensi Yuniarti. zs; Kiki Permata Sari (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2021)
ABSTRACTÂ This study aims to determine whether cash turnover affects profitability, whether environmental accounting disclosures and good corporate governance mechanisms affect financial performance and environmental accounting disclosures and whether good corporate governance mechanisms affech financial performance simultaneously. The research was conducted on manufacturing companies listed on the indonesian stock exchange in 2017-2019.This research uses purposive sampling method, with the number of companies 29 x 3 years of research and a total sample of 87. The statistical method used is SPSS multiple linear regression, with partial t statistical test hypothesis testing, simultaneous f test and coefficient of determination test.The results of this study state that: environmental accounting disclosures has a negative effect on financial performance, with a sig value of 0,361. Institutional ownership has a negative effect on financial performance, with a sig valeu of 0,980. Managerial ownership has a positive effect on financial performance, with a sig value of 0,041. The audit committee has a positive and significant effech on financial performance, with a sig valeu of 0,011. Disclosure of environmental accounting, Institutional ownership, Managerial ownership, audit committee, with a sig value of 0,021.Keywords: environmental accounting, Institutional ownership, Managerial ownership, audit committee and financial performance